APOC3-rs2854116 polymorphism related to hypercholesterolemia in primary school children in Hanoi - Thi Hong Hanh, Nguyen; Quang Binh, Tran (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 35 No 2DO - 10.25073/2588-1132/vnumps.4138, 2019)
Apolipoprotein C3 (APOC3) plays an important role in regulating lipid levels. This study aimed to assess whether the polymorphism APOC3 -rs2854116 is associated with lipid profiles in primary school children in Hanoi. A case-control study was designed including 161 cases with dyslipidemia and 406 controls without dyslipidemia. Genotype for APOC3 -rs2854116 polymorphism was determined by the polymerase chain reaction and restriction fragment length polymorphism method (PCR-RFLP). The results showed that there were differences in the effect of APOC3 -rs2854116 polymorphism to lipid profiles among children with dyslipidemia. In comparison with A/G and A/A carriers, the G/G carriers had the higher concentration of serum TC, TG, and LDL-C ( P < 0.05). APOC3 -rs2854116 polymorphism was related to hypercholesterolemia in children with the most appropriate genetic model being additive model. Increasing each of the G alleles increased the risk of hypercholesterolemia by 2.2 times ( P = 0.005) after adjustment for age and sex. This relationship was almost unchanged after adjustment for obesity-related traits. The study suggested that the APOC3 -rs2854116 polymorphism significantly associated with hypercholesterolemia in primary school children in Hanoi independent of obesity-related traits. Keywords APOC3, rs2854116, hypercholesterolemia, primary school children. References [1] A. Kawakami, M. Yoshida, Apolipoprotein CIII links dyslipidemia with atherosclerosis, Journal of atherosclerosis and thrombosis 16(1) (2009) 6-11. https://doi.org/10.5551/jat.e607. [2] D. Gaudet, D. Brisson, K. Tremblay, V.J. Alexander, W. Singleton, S.G. Hughes, J.L. Witztum, Targeting APOC3 in the familial Chylomicronemia syndrome, New England Journal of Medicine 371(23) (2014) 2200-2206. https://doi.org/10.1056/NEJMoa1400284. [3] P. Libby, Triglycerides on the rise: should we swap seats on the seesaw?, European heart journal 36 (2015) 774-776. https://doi.org/10.1093/eurheartj/ehu500. [4] W.W. Li, M.M. Dammerman, J.D. Smith, S. Metzger, J.L. Breslow, T. Leff, Common genetic variation in the promoter of the human apoC-III gene abolishes regulation by insulin and may contribute to hypertriglyceridemia, Journal of Clinical Investigation 96(6) (1995) 2601-2605. https://doi.org/10.1172/JCI118324. [5] C. Couillard, M.C. Vohl, J.C. Engert, I. Lemieux, A. Houde, N. Alméras, J. Bergeron, Effect of apoC-III gene polymorphisms on the lipoprotein-lipid profile of viscerally obese men, Journal of lipid research 44(5) (2003) 986-993. https://doi.org/10.1194/jlr.M300043-JLR200. [6] J. Dallongeville, A. Meirhaeghe, D. Cottel, J.C. Fruchart, P. Amouyel, N. Helbecque, Gender related association between genetic variations of APOC-III gene and lipid and lipoprotein variables in northern France, Atherosclerosis 150(1) (2000) 149-157. https://doi.org/10.1016/s0021-9150(99)00362-7. [7] C.A. Rocco, D. Mecikovsky, P. Aulicino., R. Bologna, L. Sen, A. Mangano, Hypercholesterolemia Is Associated with the Apolipoprotein C-III (APOC3) Genotype in Children Receiving HAART: An Eight-Year Retrospective Study, PLos One 7(7) (2012) e39678. https://doi.org/10.1371/journal.pone.0039678. [8] S. Li, Y. Yang, X. Ouyang, J. Shen, M. Zhou, Y.Y. Song, Associations of the APOC3 rs2854116 and rs2854117 polymorphisms with plasma APOC3 and lipid levels: a meta-analysis, Int J Clin Exp Med 9(8) (2016) 15972. http://www.ijcem.com/files/ijcem0025065.pdf [9] N.C. Khan, L.B. Mai, D.T.P. Ha, N.D. Minh, L.D. Tuyen, H.H Tue, Overweight, obesity and related association in adults aged 25-54 years, Nutrition status and intervention strategy in Vietnam (2007) 49-72. (in Vietnamese). [10] T.T. Mai, L.T. Hop, N.T. Lam, N.T. Xuan, Overweight, obesity and dyslipidemia in children aged 4-9 years in some primary schools of Hoan Kiem District, Hanoi. Journal of Food and Nutrition 9(3) (2013) 9-18. (in Vietnamese). [11] P.O. Kwiterovich, Recognition and management of dyslipidemia in children and adolescents, The Journal of clinical endocrinology and metabolism 93(11) (2008) 4200-4209. https://doi.org/10.1210/jc.2008-1270. [12] National Cholesterol Education Program, Report of the Expert Panel on Blood Cholesterol Levels in Children and Adolescents, Pediatrics 89(S) (1992) 525-584. https://pediatrics.aappublications.org/content/pediatrics/89/3/495.full.pdf. [13] T.G. Lohman, A.F. Roche, R. Martorell, Anthropometric standardization reference manual, Champaign, IL: Human Kinetics Book, UK (1988). [14] N.T.H. Hanh, P.T. Phuong, T.Q. Binh, APOC3 rs2854116 single nucleotide polymorphism in Hanoi primary school children, The 2nd National Scientific Conference on Biological Research and Teaching in Vietnam, Vietnam National University Publishing House (2016) 287-294. [15] X. Solé, E. Guinó, J. Valls, R. Iniesta, V. Monero, SNPStats: a web tool for the analysis of association studies, Bioinformatics 22(15) (2006) 1928-1929. https://doi.org/10.1093/bioinformatics/btl268. [16] R.L. Pollex, M.R. Ban, T.K. Young, P. Bjerregaard, S.S. Anand, S. Yusuf, M.W. Huff, Association between the-455T>C promoter polymorphism of the APOC3 gene and the metabolic syndrome in a multi-ethnic sample, BMC medical genetics 8(1) (2007) 80-87. https://dx.doi.org/10.1186%2F1471-2350-8-80. [17] N.T.H. Hanh, B.T. Nhung, L.T. Hop, T.Q. Binh, Association of nutritional status, family and neonatal characteristics with hypertriglycemia in primary school children in Hanoi. VNU Journal of Science: Natural Sciences and Technology 31(4S) (2015) 94-101 (in Vietnamese). [18] N.T.H. Hạnh, B.T. Nhung, T.Q. Binh, L.T. Hop, Optimal model on association of some environmental factors with Hyperalphalipoproteinemia in primary school children in Hanoi. Second National Conference on study and education of biology in Vietnam VNU publishing house (2016) 295-303 (in Vietnamese). [19] N.T.H. Hanh, B.T. Nhung, L.T. Hop, T.Q. Binh, Relationship between some environmental factors and hyperbetalipoproteinemia in 6 - 11 year-old children in Hanoi, Journal of Science, Hanoi National University of Education 61(9) (2016) 185-192. https://doi.org/10.18173/2354-1059.2016-0072. [20] M. Larsson, E. Vorrsjö, P. Talmud, A. Lookene, G. Olivecrona, Apolipoproteins CI and C-III inhibit lipoprotein lipase activity by displacement of the enzyme from lipid droplets, Journal of Biological Chemistry 288(47) (2013) 33997-34008. https://doi.org/10.1074/jbc.M113.495366. [21] M. Miller, J. Rhyne, H. Chen, V. Beach, R. Ericson, K. Luthra, A. Misra, APOC3 promoter polymorphisms C-482T and T-455C are associated with the metabolic syndrome, Archives of medical research 38(4) (2007) 444-451. https://doi.org/10.1016/j.arcmed.2006.10.013. [22] E.D. França, J.G.B. Alves, M.H. Hutz, APOA1/C3/A4 gene cluster variability and lipid levels in Brazilian children, Brazilian journal of medical and biological research 38(4) (2005) 535-541. http://dx.doi.org/10.1590/S0100-879X2005000400006. [23] F. Sentinelli, S. Romeo, C. Maglio, M. Incani, M.A. Burza, F. Scano, M.G. Baroni, Lack of effect of apolipoprotein C3 polymorphisms on indices of liver steatosis, lipid profile and insulin resistance in obese Southern Europeans, Lipids in health and disease 10(1) (2011). http://doi.org/10.1186/1476-511X-10-9.